THE ANALYSIS OF NON-VERBAL COMMUNICATION: HISTORY AND IMPORTANCE - Sardor Mavlonov; Shakhlo Khalilova (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract: The article is devoted to the analysis of nonverbal means of communication, its history and importance and examines the different points of view of researchers on the issue of the dominance of the type of communication in human communication. In particular, kinetic means (gestures, facial expressions, other types of body movements) are considered, which are an integral, organic part of the language system. This article draws attention to the specific features of intercultural communicative behavior.